A new species of palaemonid prawn Macrobrachium ramae sp.nov. (Malacostraca:Decapoda:Palaemonidae) from Rupnarayana River, West Bengal, India with its molecular profiles - Das, Mitali; Pahari, Priti Ranjan; Bhattacharya, Tanmay (Zootaxa, 2021)
A new species Macrobrachium ramae is described from Rupnarayana river, West Bengal, India along with its molecular characterization and Scanning electron microscopy. The species shares certain characters with M.gurudeve, M.jayasreei, M.kunjuramani and M.saengphani but differs remarkably from these species in the structure and shape of rostrum, telson, appendix masculina and in the size of the proximal segment of the antennular peduncle. Molecular characterization and phylogenetic analysis of M.ramae with mitochondrial COI and 16S rRNA genes reinforce the morphological conclusion and supports the view that it is a new species.